Lrp4 in osteoblasts suppresses bone formation and promotes osteoclastogenesis and bone resorption - Xiong, Lei (Proc Natl Acad Sci U S A, 2015)
Bone mass is maintained by balanced activity of osteoblasts and osteoclasts. Lrp4 (low-density lipoprotein receptor related protein 4) is a member of the LDL receptor family, whose mutations have been identified in patients with high–bone-mass disorders, such as sclerosteosis and van Buchem diseases. However, it remains unknown whether and how Lrp4 regulates bone-mass homeostasis in vivo. Here we provide evidence that Lrp4-null mutation or specific mutation in osteoblast-lineage cells increased cortical and trabecular bone mass, which was associated with elevated bone formation and impaired bone resorption. This phenotype was not observed in osteoclast-selective Lrp4 knockout mice. Mechanistic studies indicate that loss of Lrp4 function in osteoblast-lineage cells increased serum levels of sclerostin, a key factor for bone-mass homeostasis that interacts with Lrp4, but abolished the inhibition of Wnt/β-catenin signaling and osteoblastic differentiation by sclerostin. Concomitantly, sclerostin induction of RANKL (receptor activator of nuclear kappa B ligand) was impaired, leading to a lower ratio of RANKL over OPG (osteoprotegerin) (a key factor for osteoclastogenesis). Taken together, these results support the view for Lrp4 as a receptor of sclerostin to inhibit Wnt/β-catenin signaling and bone formation and identify Lrp4 as a critical player in bone-mass homeostasis.